MEMBANGUN KARAKTER REMAJA DALAM PERSPEKTIF PENDIDIKAN ISLAM - Ferdi Saputra; Tuti Nuriyati; Rudi Kurniawan; Maulana Ridwan (MERDEKA : Jurnal Ilmiah Multidisiplin, 2025)
The development of adolescent character from the perspective of Islamic education serves as a response to the various moral and social challenges faced by the younger generation in the modern era. Adolescent character, especially religious character, is a crucial aspect in shaping a whole, balanced, and virtuous personality. Using a descriptive qualitative method through literature review, the authors examine Islamic sources such as the Qur’an, Hadith, and scholarly perspectives to formulate effective character-building methods, including role modeling, habituation, advice, and storytelling. Islamic education is regarded as a strong spiritual and moral foundation, and it serves as an integral solution for guiding adolescents to become faithful, responsible, and positively contributing members of society. The authors hope this work provides both theoretical and practical contributions for educators, parents, and educational institutions in implementing Islamic values in the lives of adolescents.